Perfil do autocuidado de idosos diabéticos atendidos em um hospital de ensino em Belém-Pa - COTA, Aline da Silva (2023)
Objectives: To identify the adherence of self-care activities in the elderly's outpatient clinic, in a university hospital in the city of Belém. Methods: This is a cross-sectional, quantitative and descriptive study performed in diabetic patients at a elderly’s outpatient clinic teaching hospital. Were selected patients of both sexes and aged over 60 years were selected. It was applied as a evaluation instrument a socio-demographic, clinical form and the Diabetes Self-Care Activity Questionnaire (DSQ). Statistical analyzes were performed by the BioEstat 5.3 program. All the elderly people who participated in the research understood and signed the Free Consent Term (FCT). Results: Fifty-two elderly people were interviewed, of whom 69.2% were female. It was verified that 55% (n = 29) already had some complication of Diabetes Mellitus. With regard to DSQ, there was a predominance of adherence to drug therapy (96.1%), and low adherence to specific physical activities (13.46%), and consumption of five or more portions of fruit and / or vegetables (13.46%). Conclusion: Low adherence to activities that require behavioral changes, reveal the need for individualized attention and investment in Diabetes Mellitus education, considering the cognitive decline associated with aging, the economic, social and cultural factor in which patients are inserted.